Characterisation of Air Pollution on Trinidad’s North-West Coast (San Fernando to Port-of-Spain) - Baboolal, Himawatee; Balladin, Derrick (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
Air pollution is a complex mixture of toxic gases and particulates that has been identified as the largest global environmental threat facing the world today, estimated to have caused 7-10 million deaths worldwide annually [1,2]. Trinidad is the most industrialised of the Caribbean islands, with a large energy and petrochemical economic base. In addition, it is affected by seasonal Sahara dust (PM2.5). This study characterizes the baseline levels of fine and respirable particulates (three PM size fractions), trace metals in PM, gaseous pollutants and meteorological parameters at four sites over the heavily populated west coast of Trinidad during March’ 15 - May ‘16. Stations represent rural, urban, mixed background and industrial land uses. Annual mean levels of PM2.5 and PM10 in ambient air exceeded the WHO guidelines for protection of public health at all four stations (n=522). PM2.5 and PM10 exceed the WHO (2006) safe limit guidelines (PM2.5 is 10 µg/m3, PM10 is 20 µg/m3) over 70% of the time sampled at urban and industrial sites. Factor analysis indicated the variables impacting PM distribution and type of PM (size fraction) were time of year and location of station (land use). The temporal pattern for PM at the industrial station was markedly different from the other three stations, being at a constant high level throughout the year. Trace metals (in PM10) found in exceedance of Canadian (Ontario) 2012 [3] standards were, beryllium, cadmium, chromium, iron, manganese and nickel. Cd and Ni were deemed to pose the highest risk to public health as they are genotoxic carcinogens found in the smallest PM fractions. Several gaseous pollutants of concern were CO, NH3, NO2, N2O, C6H6. Nitrogen dioxide and benzene were the most prolific, being the highest most frequently at the industrial and urban stations. NO2 exceedance averaged 89% (often 2-3 times the USEPA limit for the protection of public health), reflective of the large amount of industrial combustion gases in the ambient air in the Pt. Lisas area. Benzene was found to exceed public health limit values >90% of the time measured at the urban station (Port-of-Spain) and at >80% at the mixed background station (at San Fernando). Both gases are reflective of combustion and vehicle emissions derived pollutant sources. The pollutant data was used to calculate and validate an aggregated Air Pollution Index (R2= 0.91) that could be readily applied to ongoing monitoring data in four statistically validated classification tiers; Good, Normal, High, Very High. The industrial station has the highest frequency of ‘very high’ pollutant levels, as well as the highest frequency of ‘good’ air quality days. The urban station had highest frequency of ‘normal’ to ‘high’ rankings. The rural station, as expected, had much better overall air quality. The worst air quality occurred during June-July ’15 and December ’15 -January ’16 periods. Monitoring data for air quality provides the best option to drive data driven decision making and effective air pollution management. The baseline levels of air pollutants provide adequate justification for revision of the current local regulations to afford better public health protection from unnecessarily high levels of ambient air pollution.